IbPE KERAJINAN KERAMIK DAERAH PUNDONG DAN KASIHAN, KABUPATEN BANTUL, DAERAH ISTIMEWA YOGYAKARTA - Hendri, Zulfi; Arianingrum, Retno; Widarto, - (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2015)
The long term goal of the program's science and technology for ExportProducts (IbPE) is to increase the productivity of ceramics in Small and MediumEnterprises Industries (SMI) "Soemarso Ceramics" and "Burat Kriasta"in Bantul in order to stimulate the growth of export of ceramic products. IbPE program is planned will be running for two (2) years, with specific targets to be achieved: (1) improve the quality and quantity of production to satisfy the customer or market demand by facilitating support equipment and provide training; (2) enhance customer satisfaction with the assistance of management based on ISO 9000; and (3) expand the marketing of the product through the assistance of web-based marketing strategies. Targets to be achieved in the first year is (1) to increase in the value of assets and turnover of the SMIs; and (2) to increase in the number and quality of the products marketed. The activities carried out by training and mentoring intensively, also by providing the machine production. In the first year has carried out activities for SMEs "Burat Kriasta" includes: (1) facilitation of making functional ceramic design with natural style; (2) the provision of soil mixers equipment; and (3) the preparation of the exhibition in November, while in SMEs "Soemarso Ceramics" has been carried out: (1) training and technical assistance to the manufacturing of ceramic high-temperature glaze; and (2) providing a ceramic combustion engine. In the first year, the activity has been running well. The target can be achieved in this activity is the increased value of the equipment assets of SMEs "Burat Kriasta" of 19.21%, and the turnover increased by 5%. In SMEs "Soemarso Ceramics" assets increased by 18%. In addition, an increase in the number and quality of 3) 2 the products marketed by up to 25% in SMEs "Burat Kriasta", whereas in SMEs "Soemarso Ceramics" production capacity can be increased more than 25%. Likewise, there is expansion of marketing network export to Korea in SMEs "Burat Kriasta"